Bacteriological Profile and Antibiotic Sensitivity Pattern of Urinary Tract Infection (East West Medical College Journal, 2025)
Introduction:Urinary tract infection (UTI) is a common infection that may occur in any part of the urinary system - kidneys, ureters, bladder and urethra. UTIs are caused by a wide range of pathogens, and recurrence rates of UTIs are high. Antibiotic resistance to microorganism is a burning issue all over the world due to inappropriate antibiotic use. Antibiotic resistance leads to morbidity, mortality and overall, the economic burden. Therefore, surveillance of antimicrobial resistance of UTI is essential to see its impact on population health and local treatment practices.Objective: This study was conducted to identify the bacterial agents of urinary tract infections and determine antibiogram patterns.Methods: A cross-sectional study was conducted at the outpatient service. The study included all patients who presented with UTIs and the symptoms included urinary frequency, urgency, hematuria, dysuria, and suprapubic discomfort. Those patients with clinical manifestations but are on antibiotics or antibiotics completed within the past five days were excluded.Results: The prevalence of UTI is high among females (88.67%) than males (13.33%). Among 30 samples, the pathogens implicated were Escherichia coli (E. coli) 24 (80%), Klebsiella 3. Organisms showed higher sensitivity toward Meropenem and Imipenem (100%) followed by Amikacin and Nitrofurantoin (96.6%). Isolates organisms showed high resistance levels to betalactamaes ampicillin (60%) and cephalosporines groups. According to the sensitivity profiles, the most effective oral antibiotics were Nitrofurantoin (96%) followed by Ciprofloxacin (90%).Conclusion:This study findings emphasize the significance of local antibiotic resistance patterns in urinary tract infection. More studies can be done to create local and national guidelines and physicians should use rational and adequate dose of antibiotics to avoid the emergence of antibiotic resistance.EWMCJ Vol. 13, No. 1, January 2025: 23-27